Clinical and epidemiological aspects of an outbreak of viral hepatitis E in a training centre - Pardal, Maninder Pal Singh; ., Rajiva; Rath, T. K.; Mustafa, M. S. (International Journal Of Community Medicine And Public Health, 2020)
Background: HEV infection is responsible for half of all outbreaks of acute liver disease in endemic areas. The present study deals with eighty eight cases of faeces orally transmitted Hepatitis E virus (HEV) in a regimental training center in South India in October 2016 to November 2016. Methods: Methodology and case definitions which were used for confirmed case and presumptive case of viral hepatitis were same as those which were used by Singh et al in their study. Surveillance data for all the cases was reviewed. The outbreak was described in terms of person, place and time. A sanitary survey carried out to detect the likely sources of contamination of water and to study the methods of sewage disposal with regards to septic tanks/soak pits. Results: Out of eighty-eight cases, two persons were HBsAg +ve, five were positive for both Hepatitis A and E, sixty-eight were positive for hepatitis E, five were positive for Hepatitis A, 8 persons were found negative for all the above hepatitis viruses. Overflow of sewage with foul smell and leaking water pipeline in 2 places were observed in the unit area. The overall attack rate was 27.69%. Conclusions: The present outbreak was due to faecal contamination of drinking water supplied to the regimental centre, which occurred due to old and corroded leaking pipelines in close proximity to old sewage lines having leakage through their walls. Medical authorities should maintain surveillance for all water and food borne diseases.